Right ventricular function mirrors clinical improvement with use of prostacyclin analogues in pediatric pulmonary hypertension. (February 2018) - Hopper, Rachel K.; Wang, Yan; DeMatteo, Valerie; Santo, Ashley; Kawut, Steven M.; Elci, Okan U.; Hanna, Brian D.; Mercer-Rosa, Laura
Pulmonary hypertension (PH) causes significant morbidity and mortality in children due to right ventricular (RV) failure. We sought to determine the effect of prostacyclin analogues on RV function assessed by echocardiography in children with PH. We conducted a retrospective cohort study of children with PH treated with a prostacyclin analogue (epoprostenol or treprostinil) between January 2001 and August 2015 at our center. Data were collected before initiation of treatment (baseline) and at 1–3 and 6–12 months after. Protocolized echocardiogram measurements including tricuspid annular plane systolic excursion (TAPSE) and RV global longitudinal strain were made with blinding to clinical information. Forty-nine individuals (65% female), aged 0–29 years at the time of prostacyclin initiation were included. Disease types included pulmonary arterial hypertension (idiopathic [35%], heritable [2%], and congenital heart disease-associated [18%]), developmental lung disease (43%), and chronic thromboembolic PH (2%). Participants received intravenous (IV) epoprostenol (14%) and IV/subcutaneous (SQ) (67%) or inhaled (18%) treprostinil. Over the study period, prostacyclin analogues were associated with improvement in TAPSE ( P  = 0.007), RV strain ( P  < 0.001), and qualitative RV function ( P  = 0.037) by echocardiogram, and BNP ( P  < 0.001), functional class ( P  = 0.047) and 6-min walk distance ( P  = 0.001). TAPSE and strain improved at early follow up ( P  = 0.05 and P  = 0.002, respectively) despite minimal RV pressure change. In children with PH, prostacyclin analogues are associated with an early and sustained improvement in RV function measured as TAPSE and strain as well as clinical markers of PH severity. RV strain may be a sensitive marker of RV function in this population.